PENILAIAN GURU PAMONG TERHADAP KEMAMPUAN MAHASISWA PPL DALAM MELAKSANAKAN PROSES PEMBELAJARAN DI SD - Sudin, Ali (Universitas Pendidikan Indonesia, 2017)
Teacher is one of the important keys in implementing education process. A teacher must fulfil his functions and obligations as an educator. The main task for teachers is conducting a learning process in schools. This research focuses on analyzing PPL students’s competence of UPI Sumedang class of 2012 in conducting a teaching learning process in schools. The teaching learning process consists of making teaching and learning plan and also implementing teaching and learning activities in the class. Qualitative approach which is a descriptive analysis was applied in this research. The result of the research shows that (1) in preparing teaching learning process, in general, the students achieved the competence to make teaching and learning plan by having mean score 3,5; (2) in conducting teaching and learning activities in the class, the students also achieved the mean score 3,5. Both scores proved that the students can prepare and conduct the teaching learning process relatively well.Keywords: teacher, PPL, lesson plan, teaching learning process.